Origins and Evolution of Social Medicine and Contemporary Social Medicine in Korea - Dal Sun Han; Sang-Soo Bae; Dong-Hyun Kim; Yong-jun Choi (Korean Society for Preventive Medicine, 2017)
Social medicine is recognized as one of medical specialties in many countries. However, social medicine has never been formally introduced to Korea, presumably because the term and its principles were not accepted for some years in the past in American medicine, which has strongly influenced Korean medicine. This paper describes the origins and evolution of social medicine and briefly discusses contemporary social medicine in Korea. Social medicine was initiated in France and Germany in 1848. Since then, it has expanded globally and developed in diverse ways. Included in core principles of social medicine is that social and economic conditions have important effects on health and disease, and that these relationships must be subjected to scientific investigation. The term 'social medicine' is rarely used in Korea, but many of its subject matters are incorporated into preventive medicine which, besides prevention, deals with population health that is inescapably social. However, the Korean preventive medicine directs little attention to the basic concepts and principles of social medicine, upon which systematic development of social medicine can be based. Thus, it is necessary to supplement the social medicine contents of preventive medicine through formalizing the linkages between the two fields. One way of doing so would be to change the title of 'preventive medicine' course in medical colleges to 'preventive and social medicine,' as in many other countries, and to adjust the course contents accordingly.